2021
DOI: 10.1371/journal.pone.0248395
|View full text |Cite
|
Sign up to set email alerts
|

Association between dementia and systemic rheumatic disease: A nationwide population-based study

Abstract: Objectives Systemic rheumatic disease is characterized by autoimmunity and systemic inflammation and affects multiple organs. Few studies have investigated whether autoimmune diseases increase the risk of dementia. Herein, we evaluate the relationship between systemic rheumatic disease and dementia through a population-based study using the Korean National Health Insurance Service (NHIS) claims database. Methods We conducted a nationwide population-based study using the Korean NHIS database, consisting of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 42 publications
(46 reference statements)
0
15
0
Order By: Relevance
“…After further reviewing the full text, 13 studies were excluded due to a lack of control groups or incomplete data. Ultimately, 10 studies were included in this meta-analysis ( Wu et al, 2017 ; Chang et al, 2018 ; Chen et al, 2018 , 2019 ; Liliang et al, 2018 ; Lin et al, 2018 ; Hou et al, 2019 ; Ju et al, 2019 ; Hsu et al, 2020 ; Park et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After further reviewing the full text, 13 studies were excluded due to a lack of control groups or incomplete data. Ultimately, 10 studies were included in this meta-analysis ( Wu et al, 2017 ; Chang et al, 2018 ; Chen et al, 2018 , 2019 ; Liliang et al, 2018 ; Lin et al, 2018 ; Hou et al, 2019 ; Ju et al, 2019 ; Hsu et al, 2020 ; Park et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…All included studies were published between 2017 and 2021. Of the 10 included studies, three were case-control studies ( Wu et al, 2017 ; Chen et al, 2018 ; Park et al, 2021 ) and seven were cohort studies ( Chang et al, 2018 ; Liliang et al, 2018 ; Lin et al, 2018 ; Chen et al, 2019 ; Hou et al, 2019 ; Ju et al, 2019 ; Hsu et al, 2020 ). One was conducted in South Korea ( Park et al, 2021 ), and nine reported the scenarios in China ( Wu et al, 2017 ; Chang et al, 2018 ; Chen et al, 2018 , 2019 ; Liliang et al, 2018 ; Lin et al, 2018 ; Hou et al, 2019 ; Ju et al, 2019 ; Hsu et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The primary outcome was newly diagnosed dementia and/or PD after the onset of depression in patients with IBD. Alzheimer’s dementia was diagnosed with ICD-10 codes (F00 and G30) and vascular dementia with F01 code, as defined in a previous study ( 21 , 22 ). Patients with PD were assigned both ICD-10 (G20) and V codes (V124) as defined in previous studies ( 12 , 23 ).…”
Section: Methodsmentioning
confidence: 99%